2019
DOI: 10.1128/jcm.01958-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Nucleic Acid Amplification Tests and Culture for Detection of Group B Streptococcus from Enrichment Broth

Abstract: Colonization of the gastrointestinal and genitourinary tracts of pregnant women with group B Streptococcus (GBS) can result in vertical transmission to neonates during labor/delivery. GBS infections in neonates can cause severe complications, such as sepsis, meningitis, and pneumonia. Accurate detection is critical because administration of intrapartum antibiotics can significantly reduce transmission. We compared the clinical sensitivities of three nucleic acid amplification tests (NAATs), the Hologic Panther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Rapid nucleic acid amplification tests (PCR) performed intrapartum are increasingly finding their way into clinical settings, and several studies have concluded that these screening assays perform well [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid nucleic acid amplification tests (PCR) performed intrapartum are increasingly finding their way into clinical settings, and several studies have concluded that these screening assays perform well [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Use of selective or chromogenic medium has increased the sensitivity of culture for GBS, but these methods may still be less sensitive than nucleic acid amplification tests (NAATs) for the detection of GBS ( 5 8 ). There are several commercially available NAATs for the detection of GBS that increase sensitivity, require less hands-on time, and provide a faster result, but they are often more expensive and may have slightly lower specificity than culture ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…also found that the sensitivity and specificity of GeneXpert ® and GenomEra ® PCR assays were 92.2% and 99.6%, and 92% and 96.8%, respectively ( Nielsen et al., 2020 ). NAATs were proved to be more sensitive than the post-enrichment subculture as demonstrated by the identification of GBS that were positive by NAATs assay but negative by the post-enrichment subculture method ( Buchan et al., 2015 ; Shin and Pride, 2019 ). In conclusion, NAATs offer faster time to result, greater throughput, and potentially greater sensitivity, and they are suggested as an alternative for GBS screening in pregnant women ( Rosa-Fraile and Spellerberg, 2017 ; Guo et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%